2021
DOI: 10.1021/acs.jpcc.1c03591
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conduction of Superatom Thin Films Composed of Group-V-Metal-Encapsulating Silicon-Cage Nanoclusters

Abstract: Nanocluster assembled films have attracted great interest for designing nanostructured materials with unique electromagnetic properties through a bottom-up approach. Superatoms of group-5 metals (M V = V, Nb, and Ta) encapsulating silicon (Si) cage nanoclusters (M V @Si 16 ), which are synthesized by high-power impulse magnetron sputtering technique, can be efficiently generated to form assembled films. Temperature-dependent current−voltage (I−V) characteristics of the M V @Si 16 assembled films revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…Experimental methods are briefly described, as previously reported elsewhere. 33 With the use of HiPIMS technique described in Section 2, M@Si 16 cations or anions can be generated for more than 1 nA for various central metal as shown in the mass spectra of Figure S1. Owing to the alkali metal-like nature of M@Si 16 BCSA for group-5 metal-atom encapsulation, the cations of M@Si 16 + are preferably generated for M = V, Nb, and Ta, satisfying the 68 electron shell closure.…”
Section: M@si 16 and M@ge 16 As Building Blocks For Superatom Assemblymentioning
confidence: 99%
See 3 more Smart Citations
“…Experimental methods are briefly described, as previously reported elsewhere. 33 With the use of HiPIMS technique described in Section 2, M@Si 16 cations or anions can be generated for more than 1 nA for various central metal as shown in the mass spectra of Figure S1. Owing to the alkali metal-like nature of M@Si 16 BCSA for group-5 metal-atom encapsulation, the cations of M@Si 16 + are preferably generated for M = V, Nb, and Ta, satisfying the 68 electron shell closure.…”
Section: M@si 16 and M@ge 16 As Building Blocks For Superatom Assemblymentioning
confidence: 99%
“…The electrical characteristics of group-5 metal-atom (M V = V, Nb and Ta) encapsulating Si cage BCSA (M V @Si 16 ) assembled films 33 conduction showed that ln G is not proportional to T −1 , indicating that M V @Si 16 films hardly form band structure. The electronic structures of isolated M V @Si 16 showed that singly occupied molecular orbital (SOMO) is superatomic 1H orbital with multiple nodes, making the electronic overlap of neighboring M V @Si 16 small.…”
Section: Electrical Conduction Of M@si 16 Assembled Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the electronic properties of M@Si 16 SAs have attracted much attention, as tuned by selecting the dopant central metal atoms. ,− M@Si 16 SAs can be selectively generated in the gas phase owing to their highly symmetric geometric structure and electron-shell closure of superatomic two-dimensional (2D) orbitals (68 electrons). , In fact, selective formation of M@Si 16 SAs in the gas phase has been demonstrated when the total count of valence electrons is 68 in either anionic, neutral, or cationic species; for example, Sc@Si 16 – , Ti@Si 16 , and V@Si 16 + . Recently, for use as functional nanomaterials, M@Si 16 SAs have been synthesized on the milligram scale and deposited on a substrate in a nondestructive manner, and these samples were chemically and electronically characterized in practical environments. …”
Section: Introductionmentioning
confidence: 99%